Personalised ADPCM play-back devices for the handicapped - REILLY, RICHARD (My University, 1991)
Two personalised instantaneous speech playback devices were designed and developed Both centred upon the memory efficiency advantages of Adaptive Differential Pulse Coded Modulation (ADPCM). One system is handheld and offers 64 seconds of speech. The second system hasdictionary of 230 four second phrases and is PC based.
PUBLISHED
Keywords: Administrative Staff Authors